Development of optical pH nanosensors for biological insights into the intracellular trafficking of nanomedicines - Desai, Arpan (2014)
The field of nanomedicine has progressed to a stage where a diverse set of materials are available for controlling how a drug is delivered in the body. Although these materials can be engineered to overcome many of the obstacles associated with drug delivery, the complexity of cellular trafficking mechanisms means controlling intracellular delivery remains a major challenge. The primary portal for the cellular internalisation of nanomedicines is endocytosis, which involves transport through a network of highly complex intracellular compartments undergoing a dynamic process of acidification. As a result, nanoparticle-based pH sensors offer a new perspective from which to investigate this process.